Recruitment Strategies in Makassar Traditional Culinary MSMEs: A Case Study in Losari Area - Burhanuddin, Burhanuddin (International Humanity Advance, Business & Sciences, 2025)
This qualitative study explores recruitment practices employed by traditional culinary micro, small, and medium enterprises (MSMEs) in the Losari area of Makassar. Using a case study approach, this research examines how business owners select employees based on local values, trust networks, and informal recruitment channels. The study investigates the role of kinship ties, social capital, and cultural considerations in the hiring process. Data will be collected through in-depth interviews with MSME owners and participant observation. The findings aim to provide insights into indigenous recruitment practices that differ from formal Western HRM models, contributing to understanding context-specific human resource management in emerging markets.